Democratic Republic of the Congo : Review of the 2006 Staff-Monitored Program and a New Staff-Monitored Program for 2007; Staff Report; Staff Statement; Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report, 2007)
This paper reviews the 2006 Staff-Monitored Program (SMP) and a New Staff-Monitored Program for 2007 for the Democratic Republic of the Congo. Most quantitative and structural benchmarks under the SMP for April-December 2006 were not met; nevertheless, the SMP helped prevent major financial instability during the protracted electoral period. Cognizant of the need to reestablish macroeconomic stability, the government agreed on a policy framework for 2007 to be monitored by the IMF staff. Satisfactory performance under the SMP would open the way for discussions on a new arrangement under the Poverty Reduction and Growth Facility.